Chemoresistance Mediated by ceRNA Networks Associated With the PVT1 Locus - Ogunwobi, Olorunseun O.; Kumar, Adithya (Frontiers in Oncology, 2019)
Competitive endogenous RNA (ceRNA) networks have emerged as critical regulators of carcinogenesis. Their activity is mediated by various non-coding RNAs (ncRNAs), including long non-coding RNAs and microRNAs, which competitively bind to targets, thereby modulating gene expression and activity of proteins. Of particular interest, ncRNAs encoded by the 8q24 chromosomal region are associated with the development and progression of several human cancers, most prominently lncPVT1. Chemoresistance presents a significant obstacle in the treatment of cancer and is associated with dysregulation of normal cell processes, including abnormal proliferation, differentiation, and epithelial-mesenchymal transition. CeRNA networks have been shown to regulate these processes via both direct sponging/repression and epigenetic mechanisms. Here we present a review of recent literature examining the contribution of ncRNAs encoded by the PVT1 locus and their associated ceRNA networks to the development of resistance to common chemotherapeutic agents used to treat human cancers.